Metal Content and Stable Isotope Determination in Some Commercial Beers from Romanian Markets - Cezara Voica; Dana-Alina Magdas; Ioana Feher (Journal of Chemistry)
Characterization of beer samples is of interest because their compositions affect the taste and stability of beer and, also, consumer health. In this work, the characterizations of 20 Romanian beers were performed by mean of Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and Isotope Ratio Mass Spectrometry (IRMS) in order to trace heavy metals and isotopic content of them. Major, minor, and trace metals are important in beer fermentation since they supply the appropriate environment for yeast growth and influence yeast metabolism. Beside this, the presence of the C4 plants in the brewing process was followed. Our study has shown that the analyzed beers indicated the presence of different plant types used in brewing: C3, C3-C4 mixtures, and also C4, depending on producers. Also the trace metal content of each sample is presented and discussed in this study. A comparison of the beers quality manufactured by the same producer but bottled in different type of packaging like glass, dose, or PET was made; our results show that no compositional differences among the same beer type exist.